2012
DOI: 10.21608/jppp.2012.84395
|View full text |Cite
|
Sign up to set email alerts
|

Wild Birds Injurious to Some Field Crops at Ismailia Governorate Under Field Conditions

Abstract: The wild bird species, cause serious damage to many field crops during both sowing and maturing stages. Wild birds began attacked the wheat crop after the second week of the panicles emergence. The dough stage recorded the highest percentage of damage with 9.19, 8.58 and 7.85 % at fields beside orchard, vegetables and crops respectively. While the lowest damage was recorded in the milky stage. Bird damage on Maize fields increased throughout the weeks after silking and during the development and grains growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
(2 reference statements)
0
1
0
Order By: Relevance
“…Hassan (2008) reported that, hooded crow bird caused damage on tomato at Sharkia, Qalubia and Ismailia Governorates with total value 5%, the highest percentage of damage at Ismailia Governorate followed by Qalubia Governorate and Sharkia Governorate. Abbasy et al (2012) mentioned that losses in tomato recorded high peak (19.44 & 14.54 %) followed by (18.78 & 13.73 %) during 3rd and 4th weeks at vegetable & field crops respectively. The lowest losses recorded during 7th and 1st weeks (8.83 & 11 %) followed by (9.69 & 13.56 %) in tomato nearby crops & vegetable respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Hassan (2008) reported that, hooded crow bird caused damage on tomato at Sharkia, Qalubia and Ismailia Governorates with total value 5%, the highest percentage of damage at Ismailia Governorate followed by Qalubia Governorate and Sharkia Governorate. Abbasy et al (2012) mentioned that losses in tomato recorded high peak (19.44 & 14.54 %) followed by (18.78 & 13.73 %) during 3rd and 4th weeks at vegetable & field crops respectively. The lowest losses recorded during 7th and 1st weeks (8.83 & 11 %) followed by (9.69 & 13.56 %) in tomato nearby crops & vegetable respectively.…”
Section: Introductionmentioning
confidence: 99%